Human Rights Violations and Democratic Backsliding in the Philippines under Duterte - Iglesias, Sol (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
This study examines how state-led violence under the Duterte administration in the Philippines contributed to democratic backsliding, offering critical insights for understanding human rights violations in weak democracies of the Global South. The Philippine case, marked by mass killings under the guise of an anti-drug campaign, raises urgent questions about the relationship between coercive governance and democratic erosion. While existing scholarship on democratic decline focuses largely on electoral manipulation and institutional weakening, it often under-theorises the role of systematic state violence as a mechanism of autocratisation. Building on and extending this scholarship, the study contributes to global human rights debates by foregrounding how extrajudicial violence can erode democratic norms and institutions without direct electoral interference. It argues that in contexts like the Philippines, where formal institutions remain fragile and public support for punitive policies is high, state violence operates as a powerful tool to suppress dissent, consolidate executive power, and bypass institutional resistance. Methodologically, the research employs a comparative analysis of multiple democracy datasets including the Varieties of Democracy (VDem) and the Democratic Erosion Events Dataset (DEED) to trace temporal patterns of democratic decline. By incorporating state violence as a variable, the study reveals that democratic erosion began earlier and was more deeply entrenched than conventional indicators suggest. The findings underscore the need for more robust democracy assessment frameworks that systematically integrate civil and human rights violations, particularly in the Global South, where hybrid regimes increasingly blend formal democratic institutions with violent governance practices. The study concludes that addressing democratic backsliding in such settings requires rethinking standard metrics of democracy to include coercive practices and their legitimisation through popular support. It calls for future research to explore how state violence reshapes democratic trajectories and to develop interdisciplinary methods for capturing its complex impacts on governance and human rights.